Reviving Durensewu: Providing Durian-Based Creative Dishes to Local Enterprises and Streamlining Achievements through Financial Knowledge - Joko Susilo; Dina Noviyanti; Andini Rahma Sari; Rahadian Trisna Kusuma; Anita Rizkia Rahma; Dwi Ajeng Kartikasari; Aghniya Putri Rahmatika (Indonesian Journal of Cultural and Community Development, 2024)
The aim of this service is to create innovative durian-based dishes to expand the market, increase the competitiveness of local products, and create new business opportunities in the culinary industry. In this service, the technique used involves expert chefs creating new durian-based food recipes by utilizing various durian products. Culinary creativity materialized as the provision of innovative and unique durian-based dishes, which received a positive reception from local consumers and tourists as a result of this service. This service enhances the competitiveness of local products, such as durian-based culinary innovations that increase market share, improve the competitiveness of local products, and attract tourists. In addition, business actors learn more about finance so that they can create better financial management models and support long-term sustainability. Highlights: Durian-based culinary innovation: This service focuses on creating new and unique durian dishes, expanding the market and attracting consumers. Enhanced competitiveness: Durian-based products gain market share and become more competitive due to increased creativity and positive reception. Business sustainability: Financial knowledge empowers business actors to make informed decisions and achieve long-term success. Keywords : Durian, Durensewu, Micro, Small and Medium Enterprises counseling